The contribution of the university to improve academic work of postgraduate professors - Hirsch Adler, Ana (Education Policy Analysis Archives, 2021)
The article is part of a quantitative and qualitative investigation about postgraduate professors that was developed in a public university from Central Mexico. The project had two phases: the application of a questionnaire, where we introduced open questions, and an interview program, with 10 questions, that was applied to 34 academics in that level of teaching. The purpose of the present work is the analysis of one of those questions that recuperates what was directly expressed by the subjects.: How can the university contribute to improve the academic work of the graduate professors? In the methodological part we present two procedures. The first one explains the process that was used to select the 34 academics interviewed and the second one is the definition of empirical categories, based in what the academics answered. We divided the article in two parts: a review of literature about Mexican publications and the role that the universities develop to sustain the substantive functions, and the arguments from the interviewed, classified in seven empirical categories. What they propose is that the institution should attend the following issues: find solutions to diverse bureaucratic-administrative problems, improve work conditions, take into account the questioning of the merit systems, promote support for teaching and for students, facilitate communication, develop the processes of evaluation, and foment the maturity of the collegiate bodies and review the general policies of the postgraduate studies. One of the principal conclusions is that the question How can the university contribute to improve the academic work of the graduate professors? detonated in the academics interviewed diverse concerns, reflexions, answers and proposals that can be recovered and be useful to improve our universities.